The Impact of Personal Financial Management and Emotional Intelligence on Financial Well-being with The Mediation of Risk Management Attitude - Marwan Effendi; Elva Herlianti; H Harsuti (SAFE-Network, 2024)
This study investigates the intricate relationships among personal financial management, emotional intelligence, risk management attitude, and financial well-being. The study employs a random sampling technique with a sample size of 41 individuals from Bank Mandiri KCP Solo Slamet Riyadi. Path analysis, using the SmartPLS software, is utilized to explore direct and indirect effects. The results reveal a significant positive impact of personal financial management on risk management attitude and financial well-being. However, emotional intelligence is not found to be a significant predictor of risk management attitude or financial well-being. The study concludes that effective personal financial management practices play a crucial role in enhancing financial well-being, both directly and indirectly through influencing risk management attitudes. These findings provide insights for interventions and educational programs aimed at improving individuals' financial resilience and satisfaction by emphasizing responsible financial habits and decision-making.